The Effect of the Promotional Mix in Achieving Competitive Advantage in Industrial Organizations - نعمة, رسل سلمان; الجنابي, احمد عبد محمود; محمد, مصطفى محمود (Journal of Economics and Administrative Sciences, 2020)
Purpose – determine the impact of the promotional mix in achieving competitive advantage in industrial organizations.Problem- indicated a clear deficiency in employing the dimensions of the marketing mix in ensuring a competitive advantage for the researched organization.Design/methodology/approach – Al-Dora Refinery was selected as a field of application. The sample was chosen by an intentional sample of (143) individuals in the Human Resources departments. The questionnaire was adopted as a data acquisition tool that was prepared based on a set of ready-made standards after being subjected to a number of validity and reliability tests. The statistical program (SPSS, V22) was used to enter and analyze study data.Findings – The most prominent results reached are that there are a direct relationship and a positive effect of the marketing mix in achieving competitive advantage in surveyed organizations.